Fruiting bodies of cultivating mushroom Pleurotus ostreatus as the source of immune active polysaccharides - Synytsya, Andriy; Baeva, Ekaterina; Lavrova, Ekaterina; Sushytskyi, Leonid; Bleha , Roman; Jablonsky, Ivan (Problems of Environmental Biotechnology, 2021)
This work is focused on the isolation and structural characterization of polysaccharide fractions from basidiocarps of well-cultivated oyster mushroom Pleurotus ostreatus. The fractions were obtained by subsequent extracting with water, dimethylsulphoxide, and alkali solution. The water extracts were further fractionated by preparative chromatography. The composition of the obtained purified products was determined.